The inter-nation: how international connections shaped Catalan nationhood, 1880-1920 - Duyster Borreda, J-I (2019)
This thesis examines the shifting debates on Catalan nationhood in the late nineteenth and early twentieth century. Employing a transnational approach, this thesis explores the complex role of international contacts in the making of narratives of Catalan nationhood between 1880 and 1920. It builds on and extends historiography which has explored the connection of internationalism and nationalism. In doing so, it contributes to broader debates on collective identities, particularly in peripheral regions and small nations. By drawing on extensive archival research from newspaper articles, private correspondence, pamphlets, conference proceedings and unedited manuscripts, this thesis highlights four narratives of how internationalism and nationalism reinforced each other in debates of Catalan nationhood between 1880 and 1920: (i) Nationalism as a trend, (ii) Alliance of the oppressed, (iii) Universal nationhood and (iv) Moral geography. It argues that these narratives were central in discussions of nationhood in Catalonia in the late nineteenth and twentieth century. International cultural and political connections with scholars, artists and urban planners merged in debates over the form of Catalan nationhood. Catalan nationalists sometimes acted as mediators between the different foreign perceptions of Spain and sometimes as catalysts, sharpening the distinctions made between Europe and Spain in debates over the Spanish nation-state and its empire. Examining the international contacts of Catalan nationalists in the late nineteenth and twentieth century helps to highlight the reciprocal dynamic between local, regional, national and international collective identities.